Effects of vitamin D in the nervous system: Special focus on interaction with steroid hormone signalling and a possible role in the treatment of brain cancer. (23rd October 2019) - Norlin, Maria
Abstract: The active vitamin D hormone, 1, 25‐dihydroxyvitamin D3, exerts many physiological actions in the body, including effects on the nervous system. Studies of steroidogenesis in cells of the nervous system and elsewhere not only indicate that 1, 25‐dihydroxyvitamin D3 affects steroidogenic pathways but also suggest varying responses in different cell types. For example, 1, 25‐dihydroxyvitamin D3 stimulates the expression of aromatase in human glioma but not in human neuroblastoma cells or rat astrocytes. However, in astrocytes, 1, 25‐dihydroxyvitamin D3 suppresses 3β‐hydroxysteroid dehydrogenase and steroid 17‐hydroxylase/lyase. Other studies indicate cross‐talk between vitamin D signalling and signalling of oestrogens, progesterone or glucocorticoids. Reported data indicate synergistic effects of combinations of 1, 25‐dihydroxyvitamin D3 and other steroid hormones on neuroinflammation, neurite outgrowth and neuroprotection. Also, dysregulation of steroid pathways affecting brain cells is found in vitamin D deficiency. Thus, several studies suggest that active vitamin D may affect steroid hormone synthesis and/or signalling in the nervous system, although the potential mechanisms for these responses remain unclear. 1, 25‐Dihydroxyvitamin D3 suppresses proliferation in several cell types and is therefore of interest in cancer treatment. Also, epidemiological studies associate vitamin D levels with cancer risk or outcomes. Reported data on tumours of the nervous system are mainly on glioma, a common type of brain cancer. Expression of the vitamin D receptor in glioma tumours is associated with improved survival. Several studies show that 1, 25‐dihydroxyvitamin D3 and vitamin D analogues (synthetic vitamin D‐like compounds) suppress proliferation and migration in human vitamin D receptor‐expressing glioma cell lines. Studies on mechanisms for actions of 1, 25‐dihydroxyvitamin D3 or its analogues indicate regulation of cell cycle proteins and senescence markers. These compounds also show synergism in combination with other cancer therapies treating glioma. From the data available, vitamin D analogues emerge as interesting candidates for the future improved treatment of human glioma and possibly also other cancers of the nervous system.